2002
DOI: 10.1159/000063106
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure Is Correlated with Vitamin D<sub>3</sub> Serum Levels in Dialysis Patients

Abstract: Background/Aim: The blood pressure, the most influencing factor in cardiovascular disease in end-stage renal failure patients, follows a seasonal variation during the year. Since vitamin D3 is known to be related to sun exposure, we wanted to evaluate the putative participation of the vitamin D3 metabolism in blood pressure modifications. Methods: We studied 22 stable hemodialysis patients (11 females and 11 males, mean age ± SD 56 ± 1 year) who had been continuously treated in our dialys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
20
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 18 publications
3
20
0
Order By: Relevance
“…If there are any remaining data-entry errors, they are expected to be random and not systematic. Vitamin D levels, which have been previously related to seasonal variability in BP (26) and perhaps even mortality (27), were not systematically measured.…”
Section: Discussionmentioning
confidence: 99%
“…If there are any remaining data-entry errors, they are expected to be random and not systematic. Vitamin D levels, which have been previously related to seasonal variability in BP (26) and perhaps even mortality (27), were not systematically measured.…”
Section: Discussionmentioning
confidence: 99%
“…Argiles et al [11] have reported that seasonal differences in blood vitamin D 3 levels were one of the factors in the seasonal variation of the blood pressure. In the current study, although parathyroid hormone (measured three times/year) was not assessed, ALP, which is one of the markers of the bone turnover, was highest in December, serum calcium in September, and serum phosphate was highest in February.…”
Section: Discussionmentioning
confidence: 99%
“…In most studies a higher humidity was also related to higher blood pressure values [16,18] , although humidity was not an independent predictor of blood pressure changes in the study of Cheng et al [14] .…”
mentioning
confidence: 86%
“…Increased peripheral vasoconstriction in response to a cooler environmental temperature might also be partly responsible for the higher blood pressure values during the winter period [14] . Interestingly, in the study by Argiles et al [11] seasonal differences in vitamin D3 were also related to differences in blood pressure [16] .…”
mentioning
confidence: 93%